Cognitive status in older patients with limited mobility as a predictor of negative outcome - O. N. Tkacheva; N. K. Runikhina; A. A. Reshetova; S. N. Lysenkov; M. A. Cherdak; E. A. Mkhitaryan; Ya. P. Sandakov; N. V. Sharashkina (Acta Biomedica Scientifica, 2022)
Background. Cognitive impairment (CI) is one of the important disability factors in the elderly. The role of CI in prognosis of the frailest patients with limited mobility is uncertain.The aim. To determine the influence of the initial cognitive status in the group of patronage patients aged 60 years and older on the risk of mortality within one year.Materials and methods. Study group consisted of 450 patients from patronage group with one-year period of observation (from July 2019 till July 2020). Initial physical, functional, neuropsychiatriac and social statuses were evaluated by comprehensive geriatric assessment. Cognitive impairment was screened by Mini-Mental State Examination (MMSE), with dividing patients into dementia group (MMSE ≤ 24) and no-dementia group (MMSE > 24). The mortality rate after one year was assessed.Results. Of the 450 patients included in the study, dementia was present in 44.2 %. Patients with dementia were more prone to greater severity of chronic pain, sleep disturbances, depression, malnutrition and anemia. After one year of observation 34 out of 196 patients (17.3 %) in the group of patients with dementia and 18 out of 248 patients (7.3 %; p = 0.002) in the no-dementia group died. According to multivariate analysis, independent risk factors for death in patients with dementia were anemia, hearing impairment and a history of bone fractures.Conclusion. Thus, the assessment of the cognitive status of frail patients with limited mobility is important for the purpose of identifying the most vulnerable individuals with a high risk of adverse outcomes.